Epigenetic and transcriptional control of chickpea WRKY40 promoter activity under Fusarium stress and its heterologous expression in Arabidopsis leads to enhanced resistance against bacterial pathogen. (November 2018) - Chakraborty, Joydeep; Ghosh, Prithwi; Sen, Senjuti; Das, Sampa
Highlights: Chickpea WRKY40 is a positive regulator of basal defense in plants. Fusarium infection induces histone modifications at WRKY40 promoter. Chickpea WRKY40 binds to its own promoter and negatively regulates its activity. Chickpea WRKY40 promoter is jasmonic acid inducible. Chickpea WRKY40 triggers PTI and ROS mediated cell-death. Abstract: Promoters of many defense related genes are enriched with W-box elements serving as binding sites for plant specific WRKY transcription factors. In this study, expression of WRKY40 transcription factor was analyzed in two contrasting susceptible (JG62) and resistant (WR315) genotypes of chickpea infected with Foc1. The resistant plants showed up-regulation of WRKY40 under Fusarium stress, whereas in susceptible plants WRKY40 expression was absent. Additionally, global changes in the histone modification patterns were studied in above two chickpea genotypes by immunoblotting and real-time PCR analyses under control and Fusarium infected conditions. Notably, region specific Histone 3 lysine 9 acetylation, a positive marker of transcription gets enriched at WRKY40 promoter during resistant interaction with Foc1. H3K9 Ac is less enriched at WRKY40 promoter in Foc1 infected susceptible plants. WRKY40 promoter activity was induced by jasmonic acid and pathogen treatment, while salicylic acid failed to stimulate such activity. Moreover, WRKY40 was found to bind to its own promoter and auto-regulates its activity. The present study also showed that heterologous over-expression of chickpea WRKY40 triggers defense response in Arabidopsis against Pseudomonas syringae . Overall, we present epigenetic and transcriptional control of WRKY40 in chickpea under Fusarium stress and its immunomodulatory role is tested in Arabidopsis.